Reading Comprehension Challenges Among Bilingual Students: Teachers’ Perspectives and Pedagogical Recommendations - Andriani, Diyah Iis (IJLHE: International Journal of Language, Humanities, and Education, 2025)
Reading comprehension is a fundamental component of academic success, yet bilingual students often face distinct challenges in this area, particularly in contexts where the language of instruction differs from their home language. This qualitative study investigates the reading comprehension difficulties encountered by bilingual primary school students in Indonesia, drawing on the experiences and insights of 20 classroom teachers from Tangerang Selatan, Banten. Through semi-structured interviews, the study identifies key barriers to comprehension including limited vocabulary, language interference, and low parental involvement—factors often exacerbated by socioeconomic constraints and large family sizes. The study also explores the impact of these difficulties on students’ performance in other subjects, as well as the strategies teachers employ to mitigate these challenges. Teachers propose solutions such as adapting textbooks, increasing family engagement, providing professional development in bilingual education, and enhancing early childhood programs. These findings contribute to a nuanced understanding of bilingual students' literacy development in Indonesia and underscore the need for context-sensitive educational interventions.